Avaliação nutricional da levedura torula (Candida utilis) de vinhaça em dietas para coelhos (Oryctolagus cuniculus) e cutias (Dasyprocta spp.) - Fábio Morais Hosken (2013)
The research aimed to make a nutritional evaluation of torula yeast (Candida utilis) from vinasse in diets for rabbits (Oryctolagus cuniculus) and agoutis (Dasyprocta spp.).Three experiments were conducted, two with rabbits and one with agoutis. Experiment I evaluated growth performance, carcass yield and visceral parameters in young New Zealand White rabbits, with torula yeast replacing soybean meal. Four diets were studied in a completely randomized design with four treatments and replications of 16 rabbits per diet, housed individually at 30 days of age (weaning). The treatments included 0, 5, 10 and 15% torula yeast grown on vinasse from alcohol destillery as a substitute for soybean meal in the basal diet. After 41 days, live weight at slaughter (2203, 2233, 2193 and 2228 g / animal), daily weight gain (37.49, 38.18, 37.40 and 38.03 g / animal ), total consumption (4912, 4985, 4946 and 4944 g / animal) and feed conversion ratio (3.24, 3.20, 3.25 and 3.19 kg feed intake / kg live weight gain), showed no significant difference between treatments (P> 0.05). The same occurred with carcass weight and yield, skin, liver, heart, kidney and full cecum. It was concluded that diets for growing rabbits which include torula yeast grown on vinasse from alcohol destillery, as partial or total replacement of soybean meal, do not cause significant changes in production indicators for this growth phase or in weight, carcass yield or visceral parameters. Experiment II evaluated nutritional diets with different levels of dry torula yeast from vinasse (torula) for growing rabbits, and its influence on apparent digestibility of nutrients. Using 32 New Zealand White rabbits of both sexes, four levels (control or 0%, 5%, 10% and 15%) of torula replacing the soybean were evaluated. The experimental diets were isocaloric and isoproteic. The experimental design was completely randomized with four treatments and eight replications. This test determined the digestibility coefficients of dry matter (CDMS), crude protein (CDPB), neutral detergent fiber (CDFDN), ethereal extract (CDEE) and gross energy (CDEB), and the daily average consumption. Results for the average daily consumption (113.98, 113.96, 113.22 and 115.07 g / animal / day), CDMS (71.04; 69.98, 67.79 and 74.08%), CDPB (80.17, 79.55, 75.10 and 78.47%), CDFDN (66.85, 65.50, 63.31 and 70.12%), CDEE (77.83, 76.46, 78, 36, 82.07%) and CDEB (71.04, 69.98, 68.37 and 73.82%) indicate no significant effect (P> 0.05) for intake and digestibility of diets for growing rabbits, at the four levels tested. Digestible energy (ED) and digestible protein (PD) of the test feed (torula) was also determined the by two different methods (Matterson et al.; 1965; Villamide, 1995). Estimated value of torula ED (kcal / kg DM) was 4212.74 using Matterson et al. (1965) methodology, and 4253.90, when using Villamide (1995). The estimated values of torula PD (g / kg DM) was 121.7, when using the Matterson et al. (1965) methodology, and 119.9 when using Villamide (1995). Experiment III aimed to make a nutritional evaluation of the agoutis´ maintenance diet with the inclusion of 30% torula dry yeast stillage (torula), studying its influence on apparent digestibility of the nutrients as compared to a control diet with no torula. The experiment used 20 agoutis (Dasyprocta spp.), a wildlife brazilian animal, evenly divided between both sexes. The experimental design was completely randomized with two treatments and ten replicates. The digestibility assay determined the digestibility of dry matter (CDMS), crude protein (CDPB), neutral detergent fiber (CDFDN), ethereal extract (CDEE), organic matter (CDMO), mineral matter (CDMM) and gross energy (CDEB) and the average daily consumption (CMD). The results for average daily consumption (84.48 and 90.48 g / animal / day), CDMS (67.62 and 67.06%), CDPB (71.12 and 68, l9%), CDFDN (72.70 and 69.89%), CDMM (36.27 and 33.16%) and CDMO (70.52 and 70.27%), subjected to statistical analysis showed no significant difference between treatments (P> 0.05), while the results for CDEE (63.39 and 48.04%) and CDEB (68.00 and 63.73%) differed significantly (P< 0.05). These results demonstrate a lower energy digestive capacity of this wild species when adding 30% torula to their maintenance diet, and that higher levels of inclusion may compromise intake of energy. Treatment containing torula was well consumed and the majority of coefficients studied were not affected by its inclusion, demonstrating torula vinasse to be a suitable proteic ingredient in agoutis´ maintenance diets. Digestible energy (ED) and digestible protein (PD) of torula (test food) was also estimated by two different methods (Matterson et al.; 1965) e ( Villamide, 1995). The estimated values of ED (kcal / kg DM) were 1714.22, under the Matterson et al. (1965) methodology and 1663.69, under Villamide (1995). The estimated values of PD (g / kg DM) was 259.1, for the Matterson et al. (1965) methodology and 263.2 for Villamide (1995).